Thermodynamic and Kinetic Study of Zinc bis-(Dipalmithyl Dithiophosphate) Activity as Anti-Corrosion Additive-Fatty Acid Based Through Potentiodynamic Polarization Technique - Komar Sutriah; Zainal Alim Mas’ud; Mohammad Khotib; Denar Zuliandanu (Indonesian Journal of Chemistry, 2016)
Zinc bis-(dipalmithyl dithiophosphate) (ZDTP16) is one product variant of zinc dialkyl dithiophosphate (ZDTP)-fatty acid based having function as corrosion inhibitor. By using 3% of effective dose for the application, its effectiveness of ZDTP16 corrosion inhibition will achieve 97% and it will be able to decrease Cu metal corrosion rate from 0.152 to 0.004 mm per year. Thermodynamic and kinetic parameter verification indicates the decreasing of spontaneity and corrosion rate by existence of ZDTP16 inhibitor. Gibbs free energy transition corrosion of Cu metal in electrolyte medium is measured in corrosion simulator increased from +85.22 to +91.77 kJ mol-1, while its activation energy increased from +16.66 to +33.68 kJ mol-1. Morphology observation of Cu metal substrate surface using SEM-EDX shows that the adsorption of ZDTP16 at substrate surface is able to protect surface from corrosion indicated by the existence of Zn, P, S, and C constituents representing composer atoms of ZDTP16, and the decreasing of Cl- corrosive constituent at substrate surface.